Urban dreams and realities in antiquity : remains and representations of the ancient city - Kemezis, Adam M., 1977- (Mnemosyne, Supplements, 2015)
A unique variety of approaches to all aspects of urban culture in the ancient world can be found in Urban Dreams and Realities in Antiquity , a collection of 19 essays addressing ancient cities from an interdisciplinary perspective. As the title indicates, the volume considers both how ancient people lived in their cities as physical structures and how they thought with them as ideas and symbols. Essays in this volume deal with texts and sites from Spain to South India, but there is a particular focus on the archaeology and epigraphy of Roman-era Italy, civic identity in the Roman provinces, the Hebrew Bible and Early Christian literature, Vergil and other imperial Latin authors.